Expression status of Rap1 pathway-related genes in liver metastases compared with corresponding primary colorectal cancer - Abbastabar, Maryam; Allgayer, Heike; Sepidarkish, Mahdi; Sadeghi, Farzin; Ghasemi, Maryam; Pour-bagher, Roghayeh; Parsian, Hadi (Cancers, 2024)
Understanding molecular networks of CRLM is an ongoing area of research. In this study, paired CRC tissue and adjacent noncancerous tissue from 15 non-metastatic CRC patients and paired CRC tissue and matched liver metastatic tissues from 15 CRLM patients along with their adjacent noncancerous tissues were evaluated. We assessed Rap1 pathway-related genes including NRAS, FGF-1, NGF, and KDR expression by qRT-PCR and their protein status by Western blot. In CRLM patients, NRAS, FGF1, and KDR mRNA and protein were expressed at higher levels in metastatic than in CRC primary tumor and adjacent noncancerous tissue (p < 0.05). In non-metastatic patients, NRAS, FGF1, KDR, and NGF gene expression did not differ between CRC primary tumor-and adjacent noncancerous tissue (p > 0.05). ROC curve analysis showed a reasonable diagnostic accuracy of NRAS, FGF1, KDR, and FGF for the discrimination of metastatic patients from non- metastatic ones on analysis of their primary tumors. The data suggest that further functional studies on Rap1-related genes’ role in CRLM are needed. In conclusion, the present data broaden our knowledge about specific molecular characteristics of CRLM. An increased understanding of the molecular features of metastasis has the potential to create more successful treatment, or prevention, of metastasis, especially in multimodal primary tumor treatment.
Online veröffentlicht: 29. Dezember 2023
Gesehen am 15.10.2024